MR Imaging of Cerebellopontine Angle and Internal Auditory Canal Lesions at 1.5 T - Press, Gary A.; Hesselink, John R. (American Journal of Neuroradiology, 1988)
The high-field, thin–section (3–5 mm) MR imaging characteristics of 49 cerebellopontine angle and internal auditory canal lesions were reviewed. The diverse abnormalities include 20 acoustic neurinomas, eight neurinomas of other cranial nerves (six involving the fifth cranial nerve and two involving cranial nerves IX–XI), seven meningiomas, five subdural fluid collections, four brainstem tumors with exophytic components, three glomus jugulare tumors, one epidermoid tumor, and one basilar artery aneurysm. T1-, T2-, and proton-density-weighted images were obtained in all cases. T1-weighted images most accurately showed the margins of the seventh and eighth nerves in the internal auditory canal and were most sensitive in detecting small tumors in the cerebellopontine angle. Differentiation of meningioma from acoustic neurinoma by MR was provided most reliably by separation of the meningioma from the porus acusticus and seventh and eighth nerves and not by signal-intensity differences. A hypointense vascular rim was noted on MR in seven of 13 extracanalicular acoustic tumors and in three of seven meningiomas.